American Dirt : A Novel - Cummins, Jeanine; Arizmendi, Yareli 1964- (New York, NY : Macmillan Audio, 2020)
Lydia Quixano Perez lives in the Mexican city of Acapulco. She runs a bookstore. She has a son, Luca, the love of her life, and a wonderful husband who is a journalist. And while cracks are beginning to show in Acapulco because of the drug cartels, her life is, by and large, reasonably comfortable. Even though she knows they'll never sell, Lydia stocks some of her all-time favorite books in her store. And then one day a man enters the shop to browse and comes up to the register with four books he would like to buy, two of them her favorites. Javier is erudite. He is charming. And, unbeknownst to Lydia, he is the jefe of the newest drug cartel that has gruesomely taken over the city. When Lydia's husband's tell-all profile of Javier is published, none of their lives will ever be the same. Forced to flee, Lydia and eight-year-old Luca soon find themselves miles and worlds away from their comfortable middle-class existence.
Keywords: Drug traffic -- Fiction -- Mexico; Organized crime -- Fiction -- Mexico; Immigrants -- Fiction -- Mexican-American Border Region; Audiobooks; Detective and mystery fiction; Thrillers (Fiction); Audiobooks